On the machinability of directed energy deposited Ti6Al4V - Oyelola, Olusola; Crawforth, Pete; M’Saoubi, Rachid; Clare, Adam T. (Elsevier, 2018)
Current class Directed Energy Deposition (DED) techniques used for component manufacture and repair have inherently poor geometrical tolerance. Hence, there remains a requirement to apply conventional machining strategies post build in order to achieve finished components. In contrast to wrought materials, parts produced this way have markedly different localised material properties. This in turn results in non-uniform machinability within these. The present work investigates the effect of traditional machining approaches on the processability and resultant surface integrity of Ti6Al4 V produced by DED. Here, heat treatments are applied post DED in order to homogenise the microstructure and in turn improve the overall machinability of the material. Fundamental metallurgical analysis reveals grain coarsening which is consistent with standard heat treatments used for wrought Ti6Al4 V. Investigation of the stress condition of specimens machined from the ‘as-built’ condition and the heat treated condition show a 22% increase in compressive residual surface stress, a reduction in cutting forces of 40% in the beta condition and 24% in the alpha condition at a low machining speed of 50m/min. Furthermore, heat treatment and machining strategies are proposed which demonstrate performance improvements over standard machining techniques in the ‘as-built’ condition.